Inventory of Butterlies (Lepidoptera) Sub Ordo Rhopalocera in Kedung Kopong and Banyak Angkrem, Salaman, Magelang - Rokhmah, Wakhidatur; Aliwafa, Ahmad; S, Uhuta Unggul; Rahmah, Aulya Nidaur (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Ecologically, butterflies as component in the pollination process have a role to maintain the balance of the ecosystem and enriching biodiversity. Because of that, it is important to study. It is found that the diversity of butterflies in a place is different from other places. It is because of the presence of butterflies in a habitat is closely related to environmental factors. Since there are various types of butterflies found in nature, this study was conducted to observe the type of species from the butterflies (Lepidoptera) Sub Ordo Rhopalocera that is found in Kedung Kopong and Banyak Angkrem, Salaman, Magelang. To collect the data, line transect method was applied. The length and width of the line adjusted to the topographic conditions and the stand density at the observation location. The results of this study reveals 61 species of butterflies belonging to five families. There are 9 types of Papilionidae families, 6 types of Pieridae families, 28 types of Nympalidae families, 7 types of Lycaenidae families, and 11 types of Hesperiidae families. It is found that Nympalidae family dominates the area while Peiridae is found as the less dominance.